0213 Acute Total Sleep Deprivation Impairs the Ability to Manage Response Conflict. (12th April 2019) - Salih, Rimaz; Stenson, Anthony; Sidebottom, Darian; Hinson, John; Whitney, Paul; Dongen, Hans Van; Hansen, Devon
Abstract: Introduction: The attention network test (ANT) measures the ability to use an alerting cue to detect a stimulus (alerting effect), use a spatial cue to shift the location of visual attention (orienting effect), and manage response conflict (conflict effect). Total sleep deprivation (TSD) has been shown to negatively affect cognitive functions, including distinct aspects of attention. As part of a laboratory study, we measured performance on the ANT to examine the impact of TSD on attentional functioning. Methods: 14 healthy adults (ages 21-39; 7 females/7 males) completed a 4-day (3-night) in-laboratory study. After a baseline night of sleep (9h sleep opportunity; 22:00-07:00), subjects underwent 38h TSD, followed by one night of recovery sleep (9h sleep opportunity; 22:00-07:00). A version of the ANT with variable inter-stimulus interval was administered at 09:00 during baseline, after 26h TSD, and after recovery sleep. Results: Mixed-effects analysis of variance (ANOVA) showed marked impairment in the conflict effect during TSD (F2, 26 =4.74, P=0.018). The alerting (F2, 26 =0.02, P=0.98) and orienting (F226 =0.25, P=0.78) effects were not significantly affected by TSD. Conclusion: Consistent with earlier findings, TSD did not significantly degrade the alerting effect on the ANT. In this study, TSD also did not significantly reduce the orienting effect. Thus, subjects maintained the ability to detect a stimulus and shift visual attention in response to cues, despite sleep deprivation. However, TSD had significant impact on the conflict effect, indicating that subjects experienced considerable difficulty managing response conflict while sleep-deprived. This finding is consistent with recent evidence that, independent of its effect on vigilant attention, sleep deprivation causes profound deficits in attentional flexibility. Support (If Any): Jazz Pharmaceuticals